Effects of Si on Phase Stability and Precipitation Behavior of C14 Laves Phase (Fe, Cr)2(Nb, Mo) in High Cr αFe-base Alloys. (12th February 2019) - Kimura, Yoshisato; Kato, Ko; Chai, Yaw Wang
ABSTRACT: The growth mechanism of C14 Laves phase in the bcc αFe matrix was determined as the ledge mechanism on the (110)α //(0001)C14 habit plane in Fe-20Cr-0.5Nb-1Mo (at%) alloys annealed at 1073 K for 24 hours, using conventional and scanning transmission electron microscopy. Terrace planes are the basal plane of hcp-based C14 structure. Precipitation particles tend to grow in plate shape depending on the anisotropic difference of lattice mismatch. The addition of Si with Mo remarkably enhances C14 Laves phase precipitation. The area fraction of Laves phase increases from 5.9% to 12.1% by the 2Si addition on Fe-20Cr-0.5Nb-2Mo alloys. Contrary to this, the addition of Si is not effective to increase Laves phase precipitation. It is indicated that Si improves the phase stability of C14 Laves phase while the partitioning of Mo into C14 Laves phase would be promoted due to the attractive interaction between Mo and Si.